2013
DOI: 10.4149/gpb_2013019
|View full text |Cite
|
Sign up to set email alerts
|

Potential uses of G-quadruplex-forming aptamers

Abstract: Abstract. Guanine quadruplex (G-quadruplex) structures are one of a number of structures which are capable of adopting aptamers. G-rich DNA or RNA has an increased propensity to form quadruplex structures which have unusual biophysical and biological properties. G-rich aptamers which form G-quadruplexes have several advantages over unstructured sequences: G-quadruplexes are non-immunogenic, thermodynamically and chemically stable and they have both higher resistance to various serum nucleases and an enhanced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 158 publications
0
35
0
Order By: Relevance
“…We utilized the G4 Predictor tool, G4IPDB 26 ( http://bsbe.iiti.ac.in/bsbe/ipdb/pattern2.php ), and the prevalent QGRS Mapper 27 tool ( http://bioinformatics.ramapo.edu/QGRS/index.php ) to predict the number and distribution of quadruplex-forming G-rich sequences (QGRS) with high accuracy. 27 , 28 Both HupB-4T and HupB-13T aptamers evinced high G scores (range 21–34) that was comparable or even exceeded the QGRS Mapper predicted G scores of established G-quadruplex-forming aptamers such as Thrombin 29 and anti-VEGF 30 ( Table S4 ). Analysis of these aptamers on non-denaturing PAGE provided experimental support, as both HupB-4T and HupB-13T aptamers migrated as multiple bands of higher molecular weight, unlike the control oligo 1 ( Figure 4 A), confirming formation of intra- (monomer) and inter-molecular structures (di- or tetramers) typically present in G-quadruplex-forming aptamers.…”
Section: Resultsmentioning
confidence: 93%
“…We utilized the G4 Predictor tool, G4IPDB 26 ( http://bsbe.iiti.ac.in/bsbe/ipdb/pattern2.php ), and the prevalent QGRS Mapper 27 tool ( http://bioinformatics.ramapo.edu/QGRS/index.php ) to predict the number and distribution of quadruplex-forming G-rich sequences (QGRS) with high accuracy. 27 , 28 Both HupB-4T and HupB-13T aptamers evinced high G scores (range 21–34) that was comparable or even exceeded the QGRS Mapper predicted G scores of established G-quadruplex-forming aptamers such as Thrombin 29 and anti-VEGF 30 ( Table S4 ). Analysis of these aptamers on non-denaturing PAGE provided experimental support, as both HupB-4T and HupB-13T aptamers migrated as multiple bands of higher molecular weight, unlike the control oligo 1 ( Figure 4 A), confirming formation of intra- (monomer) and inter-molecular structures (di- or tetramers) typically present in G-quadruplex-forming aptamers.…”
Section: Resultsmentioning
confidence: 93%
“…It has been reported that the combination of NMM and G-quadruplex can detect metal ions ( Liu et al, 2011 ). G-quadruplex is widely used in biosensors to detect organic molecules ( Viglasky and Hianik, 2013 ), nucleic acids ( Tang et al, 2012 ), biological enzymes ( Wang et al, 2015b )and metal ions ( Guo et al, 2012 ). In recent years, G-quadruplex based biosensors have been intensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…S4. We evaluated the interaction of the peptide-TBA conjugates with a range of agreement with those reported in literature for aptasensors [60,61], in the order of sub nanomolar discarding the SPR biosensors that enhance their sensitivity by means of amplification procedures or by exploiting the properties of nanoparticles [62].…”
Section: Spr Analysis Of the Tba-peptide Conjugates With α-Thrombinmentioning
confidence: 99%